Forensic and Pharmaceutical, Chemical and Toxicological Analysis of Medical Drugs and Substances in Illegal Circulation in Ukraine - Tkachenko, Viacheslav (SSP Modern Pharmacy and Medicine, 2023)
Recent years have witnessed a surge in the illegal circulation of medical drugs and substances in Ukraine, necessitating a comprehensive approach to their identification and analysis. This study delves into the forensic, pharmaceutical, chemical, and toxicological analyses of these substances, elucidating their origin, composition, and potential harm. Utilizing advanced chromatographic and spectroscopic techniques, the research provides an in-depth profile of commonly abused drugs and substances, many of which are cleverly disguised under seemingly benign nomenclatures. Forensic examinations highlighted the sophistication of counterfeit techniques that mimic legitimate pharmaceutical products, posing significant health risks to unsuspecting consumers. The toxicological assessments underscored the severe health implications associated with consumption, from acute poisoning to long-term physiological complications. This paper sheds light on the intricate nexus of illegal drug trafficking in Ukraine, emphasizing the urgency for robust pharmaceutical regulation, advanced forensic capabilities, and public awareness campaigns. Through its interdisciplinary approach, this research underscores the critical need for collaborative efforts among healthcare professionals, law enforcement agencies, and policymakers to combat the escalating menace of illicit drugs and safeguard public health. Fatal cases due to poisoning by psychoactive substances of various classification and legal groups were systematized. Features of forensic and pharmaceutical, chemical and toxicological analysis were indicated. Attention was focused on the classification of means and substances according to the current legislation of Ukraine. The experience of the Department of Pharmacy of the Luhansk State Medical University in Rivne for the development of forensic and pharmaceutical, chemical and toxicological analysis in Ukraine was presented.